Risk prognosis correlation of Insulin-like growth factor binding protein-3 and insulin-like growth factor-1 uterine fibroids: IGFBP-3 and IGF-1 in uterine fibroids - Lin, Tingting; Qian, Keke; Chen, Yanping; Li, Mengshu; Zhang, Zhang (Journal of Medical Biochemistry, 2025)
Objective: To explore the relationships between the levels of serum insulin-like growth factor binding protein-3 (IGFBP-3) and insulin-like growth factor 1 (IGF-1) and immune factors as well as the prognosis of patients with uterine fibroids.Methods: The study group consisted of 186 patients with uterine fibroids who had laparoscopic myomectomy between June 2023 and June 2024, whereas the control group consisted of 208 healthy women who had physical tests over the same time period. The patients in the study group were divided into a good prognosis group (84 patients) and a poor prognosis group (92 patients). The levels of GFBP-3, IGF-1 and immune factors in the study group and the control group, and their relationships with prognosis were analyzed.Results: There were ten patients who left the study group and eight who left the control group. IGFBP-3 and IGF-1 in the study group were (303.18±42.39) mg/L and (1377.11±84.78) mg/L, which both outperformed those in the control contingent [(231.25±34.18) mg/L and (438.09±52.15) mg/L] (t=12.87, 19.63) P < 0.001). Whereas the levels of CD 3+, CD 4+, and CD 4+/CD 8+ were lower than those in the control group (t=7.92, 8.41, 5.21, P < 0.001). Both values were higher [(284.63±36.19) mg/L and (434.91±53.28) mg/L]. P < 0.001 (t=5.96, 64.19). While the numbers of CD 3+, CD 4+, and CD 4+/CD 8+ cells were lower than those in the good prognosis group (t=5.31, 7.03, 3.15). There was a positive correlation between CD 8+ status and IGFBP-3, history of uterine fibroids, number of fibroids, history of miscarriage, and duration of breastfeeding (r=0.593, 0.452, 0.446, 0.419, 0.422, respectively). IGF-1 was negatively correlated with CD 3+, CD 4+, and CD 4+/CD 8+ (r=-0.720, -0.751, and -0.712, respectively). IGF-1 was positively correlated with CD 8+ status, history of uterine fibroids, number of fibroids, history of miscarriage, and duration of breastfeeding (r=0.631, 0.503, 0.444, 0.501, 0.451). Number of fibroids, a history of miscarriage, and the length of breastfeeding were risk variables that impacted uterine fibroids patients' prognosis.Conclusion: The levels of IGFBP-3, IGF-1 and CD-8+ in patients with uterine fibroids are relatively high. Moreover, IGFBP-3 and IGF-1 are related to immune factors and patient prognosis.
Keywords: Risk and prognosis; Uterine fibroids; Correlation analysis; Immune factor